Starting Early: The Benefits of Attending Early Childhood Education Programs at Age 3. (August 2019) - Ansari, Arya; Pianta, Robert C.; Whittaker, Jessica V.; Vitiello, Virginia E.; Ruzek, Erik A.
This investigation considered the short-term benefits of early childhood education participation at age 3 for 1, 213 children from low-income families living in a large and linguistically diverse county. Although no benefits emerged for executive functioning, children who participated in formal early childhood programs at the age of 3 entered prekindergarten the following year demonstrating stronger academic skills and less optimal social behavior than their peers with no earlier educational experience. However, these academic benefits were short-lived and did not persist through the end of prekindergarten, in large part because children who did not attend these programs at age 3 caught up with their classmates who did. Roughly a quarter of this convergence in academics was attributed to children's subsequent classroom experiences.